Uji Bioaktivitas Ekstrak Buah Sawo Manila (Manilkara Zapota) Terhadap Pertumbuhan Bakteri Salmonella Typhi - Salnus, Subakir; Artati, Artati (Politeknik Negeri Ujung Pandang, 2019)
This research tested the bioactive by using rawfruits of Sapodilla Sapota (Manilkara zapota) as a drag growthmedia of Salmonella Typhi bacteria causes typhoid fever disease.Salmonella typhi is a species of bacteria that are gram-negativebacilli shaped, facultative, aerobic, and moving with a singlePertrich. Sapdilla Sapota has antimicrobial activity againstSalmonella typhi, because it contains a variety of secondarymetabolite compounds such as Saponins, Tannins andFlavonoids. The purpose of this research was to know howefective the raw fruits of sapodilla sapota (Manilkara Zapota)against the growth of Salmonella typhi. This is a laboratoryyresearch by using diffusion test method. The sample of thisresearch is to extract the fruit of Sapodilla Sapota (ManilkaraZapota) crude. The results of this research are 35%concentration of extract cannot be formed drag zone (0 mm), butin 40, 45, 50 and 55% of concentration there are had drag zone (9mm, 13 mm, 13.5 mm, and 18 mm). This can be said that the rawfruit of Sapodilla Sapota extract can inhibit the growth ofSalmonella Typhi bacteria can be done, then the next extension tothe sufferers of the disease typhus to consume raw fruits ofSapodilla Sapota so that can reduce the growth of bacteria.